Efektivitas Konseling Behavioral dalam Mengurangi Kecemasan Akademik dan Meningkatkan Motivasi Belajar Mahasiswa - Sabrina Nurul Aisah; Fadhilla Yusri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to determine the effectiveness of behavioral counseling in reducing academic anxiety and increasing student learning motivation. The research method used is Single Subject Research (SSR) with a baseline-intervention-baseline design. The subject of the study was a 21-year-old female student with the initials NA, in her sixth semester, who experienced academic anxiety and decreased learning motivation due to academic pressure, part-time work, family economic conditions, and family demands. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used visual analysis of behavioral changes before and after being given behavioral counseling intervention. The results showed that before being given counseling services, the counselee experienced excessive anxiety, difficulty concentrating, sleep disorders, procrastination, social withdrawal, and decreased learning motivation. After being given behavioral counseling, more adaptive behavioral changes occurred, such as better time management skills, reduced staying up late habits, increased focus in lectures, and the re-emergence of learning enthusiasm and the ability to control anxiety. Behavioral counseling through positive reinforcement techniques, habituation of new behaviors, self-management, and relaxation exercises has been proven to be effective in helping counselees reduce academic anxiety and gradually increase learning motivation. Thus, behavioral counseling can be an effective alternative service to help students cope with academic stress and develop more positive learning behaviors.